2006
DOI: 10.1007/s10995-005-0052-0
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine and Other Substance Use During Pregnancy: Preliminary Estimates From the Infant Development, Environment, and Lifestyle (IDEAL) Study

Abstract: This is the first large-scale investigation to report the prevalence of methamphetamine use during pregnancy in areas of the United States where methamphetamine is a notable concern. Follow-up research is ongoing to investigate the outcomes associated with prenatal methamphetamine exposure. Given that this research extends and confirms previous findings showing that high-risk groups of pregnant women can be identified on the basis of basic demographic characteristics, targeted interventions are greatly needed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
106
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(111 citation statements)
references
References 40 publications
5
106
0
Order By: Relevance
“…The Substance Abuse and Mental Health Services Administration (SAMHSA) reported that among pregnant women age 15-44 years, 4.6% used illicit drugs in the previous month [42]. Consistent with the SAMHSA report, we found approximately 6% of women reported drug use during pregnancy in the multisite Infant Development, Environment and Lifestyle (IDEAL) study [2].…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…The Substance Abuse and Mental Health Services Administration (SAMHSA) reported that among pregnant women age 15-44 years, 4.6% used illicit drugs in the previous month [42]. Consistent with the SAMHSA report, we found approximately 6% of women reported drug use during pregnancy in the multisite Infant Development, Environment and Lifestyle (IDEAL) study [2].…”
Section: Introductionsupporting
confidence: 85%
“…The study was approved by the Institutional Review Boards at all participating sites. Prior to initiation of recruitment, personnel from all sites met for a week-long training session so that procedures could be standardized [2]. Recruitment is planned for two years; we present neonatal neurodevelopmental findings in the cohort recruited by year one.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tobacco is the most commonly used substance during pregnancy [16]: up to 25% of pregnant women smoke [17,18].Smoking during pregnancy causes additional health problems, including premature birth, certain birth defects, babies born too small, babies who die before they can be born at all. Smoking causes shortage of oxygen which in turn has devastating effects on baby's growth and development.…”
Section: Consequences Of Smoking During Pregnancy:-mentioning
confidence: 99%
“…The prevalence of maternal drug use during pregnancy in Canada [1] and the US [2] has been estimated to be as high as 6-10%. The consequences for the newborn are severe, and include increased risk for perinatal mortality and morbidity, as well as ongoing physical, neurobehavioral, and psychosocial problems [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%